Skip to content
Related Articles

Related Articles

Improve Article
Save Article
Like Article

Equation of parabola from its focus and directrix

  • Last Updated : 20 Sep, 2021

We are given focus(x, y) and directrix(ax + by + c) of a parabola and we have to find the equation of parabola using its focus and directrix.
Examples : 
 

Input: x1 = 0, y1 = 0, a = 2, b = 1, c = 2 
Output: equation of parabola is 16.0 x^2 + 9.0 y^2 + -12.0 x + 16.0 y + 24.0 xy + -4.0 = 0.
Input: x1 = -1, y1 = -2, a = 1, b = -2, c = 3 
Output:equation of parabola is 4.0 x^2 + 1.0 y^2 + 4.0 x + 32.0 y + 4.0 xy + 16.0 = 0. 

Attention reader! Don’t stop learning now. Get hold of all the important DSA concepts with the DSA Self Paced Course at a student-friendly price and become industry ready.  To complete your preparation from learning a language to DS Algo and many more,  please refer Complete Interview Preparation Course.

In case you wish to attend live classes with experts, please refer DSA Live Classes for Working Professionals and Competitive Programming Live for Students.

 



 

Let P(x, y) be any point on the parabola whose focus S(x1, y1) and the directrix is the straight line ax + by + c =0. 
Draw PM perpendicular from P on the directrix. then by definition pf parabola distance SP = PM 
SP^2 = PM^2 
 

(x - x1)^2 + (y - y1)^2 = ( ( a*x + b*y + c ) / (sqrt( a*a + b*b )) ) ^ 2

// let ( a*a + b*b ) = t 
 

x^2 + x1^2 - 2*x1*x + y^2 + y1^2 - 2*y1*y  = ( ( a*x + b*y + c ) ^ 2 )/ t

on cross multiplying above we get 
 

t*x^2 + t*x1^2 - 2*t*x1*x + t*y^2 + t*y1^2 - 2*t*y1*y  = ( ( a*x + b*y + c ) ^ 2 )  
t*x^2 + t*x1^2 - 2*t*x1*x + t*y^2 + t*y1^2 - 2*t*y1*y  = a^2*x^2 + b^2*y^2 + 2*a*x*b*y + c^2 + 2*c*(a*x + b*y)
t*x^2 + t*x1^2 - 2*t*x1*x + t*y^2 + t*y1^2 - 2*t*y1*y  = a^2*x^2 + b^2*y^2 + 2*a*x*b*y + c^2 + 2*c*a*x + 2*c*b*y
t*x^2 - a^2*x^2 +  t*y^2 - b^2*y^2 - 2*t*x1*x - 2*c*a*x - 2*t*y1*y - 2*c*b*y - 2*a*x*b*y - c^2  + t*x1^2 + t*y1^2 =0.

This can be compared with general form that is 
 

a*x^2 + 2*h*x*y + b*y^2 + 2*g*x + 2*f*y + c = 0.

Below is the implementation of the above : 
 

C++




// C++ program to find equation of a parbola
// using focus and directrix.
#include <bits/stdc++.h>
#include <iomanip>
#include <iostream>
#include <math.h>
 
using namespace std;
 
// Function to find equation of parabola.
void equation_parabola(float x1, float y1,
                       float a, float b, float c)
{
    float t = a * a + b * b;
    float a1 = t - (a * a);
    float b1 = t - (b * b);
    float c1 = (-2 * t * x1) - (2 * c * a);
    float d1 = (-2 * t * y1) - (2 * c * b);
    float e1 = -2 * a * b;
    float f1 = (-c * c) + (t * x1 * x1) + (t * y1 * y1);
    std::cout << std::fixed;
    std::cout << std::setprecision(1);
    cout << "equation of parabola is " << a1
         << " x^2 + " << b1 << " y^2 + "
         << c1 << " x + " << d1 << " y + "
         << e1 << " xy + " << f1 << " = 0.";
}
 
// Driver Code
int main()
{
    float x1 = 0;
    float y1 = 0;
    float a = 3;
    float b = -4;
    float c = 2;
    equation_parabola(x1, y1, a, b, c);
    return 0;
}
// This code is contributed by Amber_Saxena.

Java




// Java program to find equation of a parbola
// using focus and directrix.
import java.util.*;
 
class solution
{
 
//Function to find equation of parabola.
static void equation_parabola(float x1, float y1,
                    float a, float b, float c)
{
    float t = a * a + b * b;
    float a1 = t - (a * a);
    float b1 = t - (b * b);
    float c1 = (-2 * t * x1) - (2 * c * a);
    float d1 = (-2 * t * y1) - (2 * c * b);
    float e1 = -2 * a * b;
    float f1 = (-c * c) + (t * x1 * x1) + (t * y1 * y1);
    System.out.println( "equation of parabola is "+ a1+
                        " x^2 + " +b1 +" y^2 + "+
                        c1 + " x + " +d1 + " y + "
                        + e1+" xy + " + f1 +" = 0.");
 
}
 
// Driver Code
public static void main(String arr[])
{
    float x1 = 0;
    float y1 = 0;
    float a = 3;
    float b = -4;
    float c = 2;
    equation_parabola(x1, y1, a, b, c);
 
}
 
}

Python3




# Python3 program to find equation of a parbola
# using focus and directrix.
 
# Function to find equation of parabola.
def equation_parabola(x1, y1, a, b, c) :
  
    t = a * a + b * b
    a1 = t - (a * a)
    b1 = t - (b * b);
    c1 = (-2 * t * x1) - (2 * c * a)
    d1 = (-2 * t * y1) - (2 * c * b)
    e1 = -2 * a * b
    f1 = (-c * c) + (t * x1 * x1) + (t * y1 * y1)
    print("equation of parabola is", a1 ,"x^2 +" ,b1,
    "y^2 +",c1,"x +", d1,"y + ",e1 ,"xy +",f1,"= 0.")
 
 
# Driver Code
if __name__ == "__main__" :
 
    x1, y1, a, b, c = 0,0,3,-4,2
    equation_parabola(x1, y1, a, b, c)
 
# This code is contributed by Ryuga

C#




// C# program to find equation of a parbola
// using focus and directrix.
using System;
 
class solution
{
 
//Function to find equation of parabola.
static void equation_parabola(float x1, float y1,
                    float a, float b, float c)
{
    float t = a * a + b * b;
    float a1 = t - (a * a);
    float b1 = t - (b * b);
    float c1 = (-2 * t * x1) - (2 * c * a);
    float d1 = (-2 * t * y1) - (2 * c * b);
    float e1 = -2 * a * b;
    float f1 = (-c * c) + (t * x1 * x1) + (t * y1 * y1);
    Console.WriteLine( "equation of parabola is "+ a1+
                        " x^2 + " +b1 +" y^2 + "+
                        c1 + " x + " +d1 + " y + "
                        + e1+" xy + " + f1 +" = 0.");
 
}
 
// Driver Code
public static void Main()
{
    float x1 = 0;
    float y1 = 0;
    float a = 3;
    float b = -4;
    float c = 2;
    equation_parabola(x1, y1, a, b, c);
 
// This Code is contributed
// by shs
}
 
}

Javascript




<script>
// javascript program to find equation of a parbola
// using focus and directrix.
 
    // Function to find equation of parabola.
    function equation_parabola(x1 , y1 , a , b , c) {
        var t = a * a + b * b;
        var a1 = t - (a * a);
        var b1 = t - (b * b);
        var c1 = (-2 * t * x1) - (2 * c * a);
        var d1 = (-2 * t * y1) - (2 * c * b);
        var e1 = -2 * a * b;
        var f1 = (-c * c) + (t * x1 * x1) + (t * y1 * y1);
        document.write("equation of parabola is " + a1 + " x^2 + " + b1 + " y^2 + " + c1 + " x + " + d1 + " y + "
                + e1 + " xy + " + f1 + " = 0.");
 
    }
 
    // Driver Code
        var x1 = 0;
        var y1 = 0;
        var a = 3;
        var b = -4;
        var c = 2;
        equation_parabola(x1, y1, a, b, c);
 
// This code contributed by gauravrajput1
</script>
Output: 
equation of parabola is 16.0 x^2 + 9.0 y^2 + -12.0 x + 16.0 y + 24.0 xy + -4.0 = 0.

 




My Personal Notes arrow_drop_up
Recommended Articles
Page :